Pengaruh Kualitas Produk, Citra Merek dan Harga dalam Mempengaruhi Keputusan Pembelian Smartphone Android - Haifan Tri Buwono Joyo Pangestu; Fenilinas Adi Artanto (MAMEN: Jurnal Manajemen, 2024)
This research aims to analyze factors that can influence the decision to purchase an Android smartphone  in the Pekalongan Regency area using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The factors studied are product quality (X1), brand image (X2), and price (X3). From distributing the questionnaire, it was found that the number of respondents was 53 people who were selected using the purposive sampling method, namely Android smartphone  users in the Pekalongan Regency area. The majority of respondents obtained were male students who worked as students. The data collected was analyzed using SmartPLS 3 software. The results showed that the variables product quality (X1), brand image (X2), and price (X3) had a significantly positive influence on purchasing decisions for Android smartphone s in the Pekalongan Regency area. The R-square value obtained was 0.979, which indicated that the variables product quality, brand image and price had an influence of 97.9% in the decision to purchase an Android smartphone . Apart from that, each variable also has a P-value of less than 0.05, which shows that there is a significant relationship between these variables and the decision to purchase an Android smartphone  in the Pekalongan Regency area.